Some left to tell the tale: Finding perpetrators and understanding violence in Rwanda. (July 2020) - Loyle, Cyanne E; Davenport, Christian
Scholars of political violence often face problems concerning data availability. Research on the perpetrators of that violence is no exception. Over the past 40 years we have made great strides in understanding who joins in violent action and why, yet have rarely probed the representative nature of the subjects queried or contemplated the implications of this sampling for our conclusions. It is generally assumed that those left to 'tell the tale' about what transpired are representative of those who participated in the violence. In this article, we use the context of the 1994 genocide in Rwanda to probe questions about which perpetrators of violence we include in our research and subsequently, who we miss. We theorize an often overlooked group of perpetrators, the 'murderers in the middle', who take orders from above, mobilize others to kill, and zealously participate themselves. We contend that this group of perpetrators is potentially unique from those generally captured, identified, and studied in that they are likely to have actively and willingly engaged in violence for personal gain as well as for ideological reasons. Systematically missing groups of perpetrators has potential implications for research on participation in mass violence as well as our understanding of why this behavior occurs.